Office densification effects on comfort, energy, and carbon lifecycle performance: An integrated and exploratory study. (April 2020) - Hoxha, E.; Liardet, C.; Jusselme, T.
Highlights: This research measured the environmental impacts of office densification. Densification did not significantly impacted the occupant's comfort. Environmental impacts (CED, CEDnr, GWP) were reduced by almost 50 %. A new functional unit "eq-nominal people per effective presence" is introduced. Abstract: Generally, the environmental impacts of buildings are benchmarked per square meter as a functional unit. However, this practice prevents developing a user-centered approach in which performance is linked to real usage and not building size. Currently, the less a building is used, the lower the energy consumed during its use and, consequently, the impact per square meter, which does not make sense regarding both usability and environmental performance. Following user-centered design principles, the goal of the present research is to assess the environmental impact of buildings based on novel user-based functional units and to understand the environmental impact consequences of office occupation density. An experiment within the area of an academic office offered the opportunity to test the densification of working spaces and evaluate the resulting environmental and comfort impacts. In the end, the new user-based functional units highlight a reduction of all environmental indicators by almost 50 %. Also, the functional unit "eq-nominal people per effective presence" is introduced as most suitable to evaluate environmental performance according to real building usage, as a complement to square meter function units.